Ethics of Da'wah Messages - Farhan Dimas Subagja (Sahabat Publikasi, 2026)
The message of da'wah serves as a strategic medium for conveying Islamic values to the broader community. However, the success of the da'wah message is largely determined by the ethical aspects that underlie it. This article aims to conceptually examine the ethical principles in delivering da'wah messages based on the Mabadi 'Asyarah approach developed by Dr. Tata Sukayat, supported by academic studies from UIN Sunan Gunung Djati Bandung. Using a qualitative literature study method, this article finds that values such as honesty, compassion, wisdom, and humility (tawadhu) are essential elements in shaping an effective, inclusive, and sustainable da'wah message. Ethics are not merely complementary elements in da'wah but constitute the core foundation that determines the success and sustainability of Islamic communication. The theoretical implications of this study affirm the importance of integrating ethics into any contemporary da'wah strategy, while practically, this article recommends strengthening communication ethics education for today's preachers.